Mutation rates and segregation data on 16 Y-STRs: An update to previous GHEP-ISFG studies. (December 2017) - Antão-Sousa, S.; Sánchez-Diz, P.; Abovich, M.; Alvarez, J.C.; Carvalho, E.F.; Silva, C.M.D.; Domingues, P.; Farfán, M.J.; Gutierrez, A.; Pontes, L.; Porto, M.J.; Posada, Y.; et al.
Abstract: The increasing relevance of human Y-STRs in forensic science demands reliable estimates of their mutation rates. Therefore, a collaborative study was carried out by the Spanish and Portuguese working group of the International Society for Forensic Genetics (GHEP-ISFG) in the interest of extending the data on Y-chromosomal short tandem repeat (Y-STR) mutation rates. Sixteen Y-STRs were considered in the analyses: DYS456, DYS389I, DYS389II, DYS390, DYS458, DYS19, DYS385, DYS391, DYS392, DYS393, DYS439, DYS635, DYS437, DYS438, DYS448, GATA H4. Among the sample of 1598 father-son duos analyzed, 46 mutations were observed, 45 of which were a single-step change and 1 was a double-step change. A total of 28 repeat losses were observed against 18 gains, with a ratio of 1:1.5. Eleven duos showing double alleles at the Y-STR loci DYS19, DYS391, DYS439 and DYS448 without allelic discrepancy between the father-son duo were also observed. This new data was added to the previous studies from the GHEP-ISFG working group, totalizing 63 496 allele transmissions (varying between 2298 and 7347 per locus). The average mutation rate across all 16 Y-STRs loci was 0.00187 (95% CI 0.00155–0.00224). The average mutation rates per marker varied between 0.00057 (95% CI 0.00007–0.00206) at DYS438 and 0.00606 (95% CI 0.00375–0.00925) at DYS439.